2021
DOI: 10.3390/nu14010019
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Fish Species for Nutritional Management of Children with Fish-FPIES—A Clinical Approach

Abstract: In the Mediterranean region, fish is a common cause of food protein-induced enterocolitis syndrome (FPIES) in children. No laboratory tests specific to FPIES are available, and oral food challenge (OFC) is the gold standard for its diagnosis and testing for achievement of tolerance. Children with FPIES to fish are usually advised to avoid all fish, regardless of the species. Fish are typically classified into bony and cartilaginous, which are phylogenetically distant species and therefore contain less cross-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…A total of three/eight children with FPIES from one or more fish species tolerated other types of fish [ 44 ]. Furthermore, testing tolerance to a fish different from the one responsible for the adverse reaction is important because it could prevent excessive nutritional restrictions and favor oral tolerance induction [ 103 ]. Gonzalez-Delgado et al reported a series of 16 children with fish-induced FPIES.…”
Section: Prognosis and Natural Historymentioning
confidence: 99%
“…A total of three/eight children with FPIES from one or more fish species tolerated other types of fish [ 44 ]. Furthermore, testing tolerance to a fish different from the one responsible for the adverse reaction is important because it could prevent excessive nutritional restrictions and favor oral tolerance induction [ 103 ]. Gonzalez-Delgado et al reported a series of 16 children with fish-induced FPIES.…”
Section: Prognosis and Natural Historymentioning
confidence: 99%